Analysis of The Influence of Information Quality, Ease of Use, and Trust on Online Purchase Decisions on Shopee (Research On Users Of The Shopee E-Commerce Platform At Muhammadiyah University Yogyakarta) - Inggaris, Agil Fatasyan; Wibowo, Sutrisno (UIN Sunan Kalijaga Yogyakarta, 2023)
Research Aims: This study aims to analyze of the influence of information quality, ease of use, and trust on online purchase decisions on shopee (study of shopee.co.id buying and selling site users at yogyakarta muhammadiyah university). Methodology: The study employs a quantitative survey approach, targeting all students, particularly female students, at Muhammadiyah University of Yogyakarta. The sample comprises 100 respondents from the Faculty of Economics and Business. The data analysis involves Multiple Linear Regression, Simultaneous Significance Test (F Test), Individual Parameter Significance Test (t-test), and Coefficient of Determination Analysis (R²). Research Findings: The findings indicate a notable and positive impact of information quality, ease of use, and mutual trust on online purchasing decisions at Shopee. Specifically, information quality, ease of use, and trust each individually exhibit a significant positive influence on online purchasing decisions at Shopee. Theoretical Contribution: The theoretical contribution of this research lies in its comprehensive assessment of multiple factors and their individual impacts on online purchasing decisions. The study enriches existing theoretical frameworks related to e-commerce and consumer behavior, paving the way for more nuanced and context-specific investigations in the field. Implication: The implications suggest actionable steps for Shopee to enhance its online platform, build trust, and tailor strategies to influence information quality, ease of use, and trust for more effective online purchasing decisions.